EKSPRESI ROMANTIS DALAM KUMPULAN CERPEN TUNGGU AKU DI SUNGAI DUKU KARYA HARY B KORI’UN - Purwanto, Tri Yudha; ', Elmustian; Rumadi, Hadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is titled Romantic Expression in a Collection of Short Story Tunggu Aku di Sungai Duku written by Hary B Kori’un. The method used in this research is a descriptive analysis method by using qualitative approach. The data of this research are romantic expressions in the collection of short story Tunggu Aku di Sungai Duku written by Hary B Kori’un and published by Palagan Press containing eleven short stories using more backgrounds in Pekanbaru. In the result of this research, there are 63 happiness romantic expressions and sadness romantic expressions. Happiness romantic expression consists of five indicators, i.e. quiet and peaceful feelings, happiness, love, freedom, and optimism. However, sadness romantic expression consists of eight indicators, i.e. sadness, condolence, misfortune, loss, brittleness, unhappiness, unpleasantness, pain, and misery. As regard for the data included in the aspect of happiness romantic expressions amount to 33 data. However, the data included in the aspect of sadness romantic expressions only amount to 30 data. Happiness romantic expressions aroused by the author are influenced a lot by the freedom indicator, whereas sadness romantic expressions are influenced by loss indicator.Key Words: Romantic, Expression, Short Story.